EXAMINATION OF LEAD (PB) AND CADMIUM (CD) HEAVY METAL CONTAMINATION IN VARIOUS TYPES OF FISH IN EAST JAKARTA - Wulansari, Devi; Harfani, Pilar Syifa; Permadi, Aef; Soeprijadi, Liliek; Napitupulu, Romauli Juliana (Politeknik Kelautan dan Perikanan Karawang, 2026)
Heavy metal contamination poses a chemical hazard in food. Monitoring waste parameters, including toxic metals such as lead (Pb) and cadmium (Cd), is essential. Contaminated seafood is a primary source of human exposure to heavy metals. This study aims to determine the levels of lead (Pb) and cadmium (Cd) in various types of fish before consumption to ensure that the fish consumed are safe for consumers. Heavy metal testing using Atomic Absorption Spectroscopy (AAS) revealed that kerang dara (Anadara granosa) contained the highest levels of lead at 0.383 mg/kg and cadmium at 0.479 mg/kg. These levels do not exceed the maximum limits specified in SNI 7387:2009 on